Milk yield and reproductive performance of crossbred holstein í— criollo limonero cows - Zambrano, Sunny; Contreras, Gloria; Pirela, Manuel; Cañas, Homero; Olson, Tim; Landaeta Hernández, Antonio (Revista Científica de la Facultad de Ciencias Veterinarias, 2010)
Records from Â½ Criollo Limonero + Â½ Holstein (F1) and backcrosses, Â¾ Criollo Limonero + Â¼ Holstein (R) handled in a Venezuelan humid tropical forest zone were analyzed to compare their productive and reproductive performance. The analyzed variables were: age at first calving (AFC), interval from calving to conception (ICC), calving interval (CI), services per conception (SC), gestation length (GL), calf birth weight (CBW), lactation length (LL), milk at 90 d (M90), total milk yield (TMY), and milk adjusted to 305 d (M305). No statistical differences (P > 0.05) were found between F1 and R for AFC (3.4 Ó 0.1 vs 3.2 Ó 0.1 years), SC (1.6 Ó 0.1 vs 1.7 Ó 0.1), GL (both 280d), CBW (both 34 Ó 0.6 kg), M90 (919 Ó 99 vs 813 Ó 105 kg), TMY (2093 Ó 176 vs 1964 Ó 176 kg) or for M305 (2424 Ó 146 vs 2430 Ó 151kg), respectively. However, the F1 cows had ICC (258 Ó 18 vs 173 Ó 22 d; P < 0.004) and CI (577 Ó 21 vs 474 Ó 25 d; P < 0.001) longer than R, respectively. Year of birth affected (P < 0.05) to AFC, (P < 0.03) to ICC, and (P < 0.01) to CI, M90, TMY, and M305. Environmental effects were found for GL, M90, TMY, M305, and LL. Although no differences between genotypes were found for milk yield, R cows had better reproductive performance than the F1 cows.